#Ledatoo: The morality of Leda and the Swan in teaching stylistics. (May 2021) - Cook, Guy
The article discusses the morality of W. B. Yeats' sonnet Leda and the Swan in the context of a widening gap between the sexual mores of earlier times and our own, and whether the poem remains a suitable choice for the teaching of stylistics. I begin by examining stylistics treatments of the poem, and its political, social and artistic context, then move on to consider charges of misogyny against the poem for eroticising and failing to condemn the rape it depicts. To assess these charges I examine other literary uses of the Leda myth both before and after Yeats, including earlier poems which romanticise the rape, and later ones which vilify it. I also consider the implications of my discussion for the teaching of other canonical poems on similar themes. The last part of the paper discusses more generally the place of morality in literature and literature teaching, including stylistics: whether teachers and analysts should promote a moral world view and moral behaviour through their choice of texts and comments on them, or whether there are other valid criteria for selecting and describing a text such as Leda and the Swan . To elucidate current views, I draw parallels with the moral didacticism of the highly influential literary critic F. R. Leavis in the mid twentieth century, and ask whether aspects of his patrician view have undergone a surreptitious revival in some contemporary pedagogy and criticism at the beginning of the twenty first.